Substrates based on carbonized rice husk alter strawberry productivity in a semi-hydroponic system (Research, Society and Development, 2022)
The production of strawberry in the semi-hydroponic system still has several unknowns to be answered, one of them is to make the system less costly because this crop has a high implementation cost. The choice of the ideal substrate is one of the biggest doubts of the producer, as it can generate high costs when purchased commercially. For this, rice husk becomes an alternative to replace other substrates because it is an easily available and inexpensive material in rice regions of Brazil. The objective of this work was to evaluate and compare the productive performance of strawberry cv. Albion cultivated in different substrate compositions under the semi-hydroponic system. The exclusive use of charred rice husk was not beneficial because it reduced growth variables and crop yield. In the production of strawberry cv. Albion in polypropylene gutter system, the use of 25% commercial substrate amount is enough to maintain the productivity and quality of pseudofruits, in addition to further reducing the system implementation costs by using charred rice husk as substrate constituent. Include the abstract in English.